1976
DOI: 10.4315/0022-2747-39.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Survey of Frankfurters Produced at Establishments Under Federal Inspection

Abstract: At the time of manufacture, 78% of 69 sets of packaged frankfurters collected from 40 firms had aerobic plate counts of 10,000 or fewer/g and 90% had 20,000 or fewer/g (geometric means of 10 units/set), 91% were coliform-negative, and 93% were Staphylococcus aureus-negative. Only one of 690 packaged frankfurter units was Escherichia coli-positive, and all units were salmonellae-negative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

1977
1977
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
1
5
0
1
Order By: Relevance
“…The use of a salt-containing medium could give misleading information regarding the ability of the heating step to kill staphylococci if a frankfurter were heated to only 140°F. However, in our process and in most commercial ones (15), the product is heated to ca. 160°F, which is equivalent to a thermal exposure of ca.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of a salt-containing medium could give misleading information regarding the ability of the heating step to kill staphylococci if a frankfurter were heated to only 140°F. However, in our process and in most commercial ones (15), the product is heated to ca. 160°F, which is equivalent to a thermal exposure of ca.…”
Section: Resultsmentioning
confidence: 99%
“…The data presented here on the thermal destruction of S. aureus during frankfurter processing provide support for and confirmation of the observations of Surkiewicz et al (15) that frankfurters are staphylococci-free after being processed and before being peeled. Surkiewicz et al (15), in several commercial plants, observed that most frankfurters produced under federal inspection are heated to an internal temperature of 69 to 71.10C (158 to 160°F), the lowest temperature observed being 660C (150.8°F) and the highest 820C (179.6°F). They determined that all 127 samples of cooked frankfurters were S. aureus-free before being peeled and packaged.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in contamination of beef due to industry changes could have influenced the number of outbreaks. Although studies and sampling programs have varied over time, one USDA survey in 1975 reported that only 0.4% of raw beef patties sampled were contaminated with salmonella [34], whereas USDA-FSIS reported an estimated 7.5% prevalence in ground beef samples in 1993–1994 [10] and <3% in the 2000s [9]. In addition, proactive decisions by USDA-FSIS in ground beef outbreak investigations might have also contributed to the increase.…”
Section: Discussionmentioning
confidence: 99%
“…The total figure of 29-7 % of packets from which salmonellas were isolated is comparable with the results reported by other workers. Galton, Lowery & Hardy (1954) found salmonellas in 23 % of fresh sausages, Weissman & Carpenter (1969) reported an isolation rate of 38-3 % and Surkiewicz, Johnston, Elliott & Simmons (1972) found 28 % of samples of pork trimmings and 28 % of finished sausages contaminated with salmonellas.…”
Section: Discussionmentioning
confidence: 99%